Tryptophan Hydroxylase 1 Variant rs1800532 is Associated with Suicide Attempt in Serbian Psychiatric Patients but does not Moderate the Effect of Recent Stressful Life Events. Issue 6 (2nd April 2016) - Karanović, Jelena; Ivković, Maja; Jovanović, Vladimir M.; Pantović, Maja; Pavlović‐Janković, Nataša; Damjanović, Aleksandar; Brajušković, Goran; Romac, Stanka; Savić‐Pavićević, Dušanka
Abstract : Tryptophan hydroxylase 1 (TPH1) gene, coding for serotonin synthesizing enzyme, and recent stressful life events (SLEs) have been commonly associated with suicidal behavior. TPH1 has been also hypothesized to be involved in stress–response mechanisms. The aim of this study was to assess TPH1 variant rs1800532 and its possible interaction with recent SLEs as risk factors for suicide attempt (SA) in Serbian psychiatric patients, including 165 suicide attempters and 188 suicide nonattempters. rs1800532 and recent SLEs were independently associated with SA, while rs1800532 did not moderate the effect of recent SLEs on SA vulnerability among Serbian psychiatric patients.